KAJIAN POPULASI DAN STRUKTUR KOMPOSISI VEGETASI HABITAT BUNGA BANGKAI (Amorphophallus titanum [Becc.] Becc. Ex Arcang) DI KAWASAN HUTAN BENGKULU - wahyudi arianto (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Abstract. The knowledge on structure and composition of Titan Arum habitats in lowland tropical rain forests of Bengkulu limit the option to formulate the appropriate strategy for conservation. The research was carried out with objective to determine the structure and composition of vegetation in the habitats located in Bengkulu. This study used purposively sampled plot with a size of 100 m x 100 m consisting of sub-plot of 20m x 20m, 10 m x 10 m, 5 m x 5 m and 2 m x 2 m for observing tree, pole, sapling and seedling. Data were analyzed to generate the following parameters: important value index (IV), diversity index of Shannon-Wienner and evenness index, interspecific association and resemblance function. The results showed that the total number of Titan Arum individuals found across 3 sampled forest sites were 52 individuals, consisting of 49 individuals at vegetative phase and 3 individuals at generative phase. Titan Arum habitats consisted of 417 species belonging to 103 families of various growth stages. Habitat in Air Selimang was dominated by Artocarpus elasticus with an important value index of 12.09%, while in Tebat Monok and Palak Siring were by Quercus oidocarpa with IV of 22.22% and Elatoriospermum tapos with IV of 31.40%, respectively. Values of diversity indices (H’) of vegetation for Titan Arum habitats for each growth stages were nearly steady (2.75 – 4.50). A similar steady trend was also observed for evenness index values of 0.640 – 0.982 at each growth stages. The vegetation of Titan Arum in Air Selimang and Tebat Monok revelaed positive interspecific association for all species, whereas in the Palak Siring habitat showed independence of species. Air Selimang Vegetation has the greatest resemblance to Tebat Monok with similarity index of 62.26. .